An integral approach for management challenges in the dairy industry - Herrera, Natalia, author; Pinedo, Pablo, advisor; Velez, Juan Santiago, committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2023)
A growing body of literature recognizes the importance of including an integrated approach to animal welfare and employee well-being in the dairy industry. The current thesis aims to describe this integral approach by presenting two research projects developed in a commercial dairy under the same management. Hence, an animal welfare pilot study was performed on a dairy farm located in northern Colorado, and an employee well-being study was developed on three dairy farms, two located in northern Colorado and one in northern Texas. Both projects were performed during the year 2022 and the dairies are administrated by the same management. The overall structure of this thesis takes the form of three chapters, including each perspective previously analyzed in the current management challenges explored in the dairy industry. Chapter one presents an extensive literature review of both approaches identified as management challenges in the dairy industry. Then, chapter two analyses the results of an online survey undertaken from September through November 2022 that aimed to explore employee adaptation, perception, and understanding of technology in the dairy farm. In order to accomplish the goal of this pilot study, the online survey completed by two-hundred-sixty-six employees was analyzed and the results are presented in chapter two. Chapter three presents the results of an observational study done on cow-calf behavior from the expulsion of the calf up to the separation in a dairy system located in northern Colorado. One-hundred-sixty-seven calving that occurred from May to June were analyzed and the results are presented in chapter three. Results are briefly described next. First, from the adaptation, perception, and understanding of technology in the dairy farm study, employees recognize and have positive feelings towards the technology implemented at work, where they highlighted the understanding of its benefits, and recognized the technology as a tool that helps them to be more efficient. However, the challenges to adapting to new technology were mainly determined to be personal limitations, such as not knowing the language of the technology and impairments to seeing. Also environmental limitations were recognized by the employees such as cold weather, wind, or an environment that is too dark or too bright. Lastly, the level of perception of technology was found to be associated with the level of education and level of English of the employee, but no significant differences were identified by age or gender. Findings are promising and the current thesis invites the academia to extended this type of research in other livestock operations that adopt precision livestock farming technology. Second, from the cow-calf behavior from the expulsion of the calf up to separation in a dairy system research, with an average time of 2,489 seconds together, the predominant behavior found by the dam was the intensive licking towards their calf, and secondary particular behaviors were lying down after calving, aggressive behavior upon a surrogate cow, and a following behavior upon separation. On the calf side, the main behaviors were licking the cow, and mobilizing with their two front hooves. Less common behaviors were standing up, reaching the udder, suckling, and looking at her cow upon separation. Moreover, animal-level variables that were associated with these behaviors were found to be parity and calving difficulty. Also, for environmental-level variables, the drop time, calving in the patio, and temperature were associated with these behaviors as well. In general, no significant associations were found for twins, calf gender, and heat index. Lastly, when the future health performance of both animals was analyzed, only the stand-up behavior of the calf was significantly associated with an increased average daily gain weight from birth to weaning, compared to calves that did not stand up. The novel findings presented in this thesis will help dairy management to better understand latent challenges in the industry with an integral approach that includes animal welfare and employee well-being. This study extends the knowledge of cow-calf contact systems by exploring the animal behavior right after calving and up to separation and provides a comprehensive assessment of adaptation, perception, and understanding of precision livestock farming technologies by the dairy employee. The conclusions from this thesis will add to the rapidly expanding field of integrating animal and employee health into integral strategies for current management challenges in the dairy industry.
Keywords: cow-calf contact; management; technology; dairy; animal behavior; precision livestock technology